Gastrointestinal Symptoms in Relation to Quality of Life After Metabolic Surgery in Adolescents - Dewberry, Lindel (Surg Obes Relat Dis, 2020)
BACKGROUND: Adolescent obesity is associated with significant comorbidities including decreased quality of life (QOL). QOL improves after metabolic and bariatric surgery (MBS), but recent studies have demonstrated that certain gastrointestinal symptoms (GIS) worsen after surgery, including reflux symptoms, nausea, bloating and diarrhea. OBJECTIVE: The aim of this study was to evaluate QOL and the effect of these symptoms on QOL after bariatric surgery. SETTING: Five academic centers performing adolescent MBS in the United States. METHODS: We prospectively studied 228 adolescents undergoing MBS using the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) cohort. Gastrointestinal symptoms and QOL scores were assessed before surgery, at 6-months and yearly to 5 years after surgery. Analysis involved linear models examining QOL and the association between GIS and QOL adjusting for a priori determined covariates. RESULTS: Adjusting for body mass index (BMI) change over time, the physical component score (PCS) of the Short Form-36 (SF-36) increased after surgery from 44.2 at baseline to 54.4 at 5 years (p<0.0001). The mental component score (MCS) did not significantly change over time. The SF-36 domains that showed the biggest increase after surgery were physical functioning, physical role functioning, and general health. The SF-36 PCS decreased significantly over time post-surgery in those with GIS of reflux, nausea, and diarrhea but remained higher than baseline SF-36 PCS. There was no statistically significant change in MCS or IWQOL-KIDS scores in those with or without GIS. CONCLUSION: QOL, specifically the SF-36 PCS, increases after MBS. Reflux symptoms, nausea, and diarrhea reduce the degree of improvement in QOL in adolescents following MBS. Patients should be monitored and treated for these symptoms to address this decreased QOL.